(untitled) (Acta Scientiarum. Health Sciences, 2014)
Current study develops and validates a dissolution test for Prasugrel hydrochloride 10 mg in coated tablets. After sink condition, filters and drug stability were evaluated, the discriminatory dissolution conditions were achieved with a USP apparatus 1 (basket) at 50 rpm stirring speed and 900 mL of 0.01 M HCl as dissolution medium. The UV spectrometric method at 220 nm was performed and validated for the determination of Prasugrel. The parameters specificity, linearity, accuracy, precision and robustness were evaluated according to international protocols. UV method and dissolution test proposed in current analysis may be applied for quality control of coated tablets containing Prasugrel since there is no official monograph for this drug.